Meltdown: Reading Kernel Memory from User Space: Lessons learned from Meltdown's exploitation of the weaknesses in today's processors. - LIPP, MORITZ; SCHWARZ, MICHAEL; GRUSS, DANIEL; PRESCHER, THOMAS; HAAS, WERNER; HORN, JANN; MANGARD, STEFAN; KOCHER, PAUL; GENKIN, DANIEL; YAROM, YUVAL; HAMBURG, MIKE; STRACKX, RAOUL (Communications of the ACM, 2020)
The article presents Meltdown and discusses its performance, evaluation, and countermeasures. According to the article, Meltdown is an attack which exploits hardware vulnerabilities in the way the processor enforces memory isolation. The authors note that it successfully leaked kernel memory on unpatched operating systems including Linux, Windows, and Android.